2022
DOI: 10.3389/fimmu.2022.959697
|View full text |Cite
|
Sign up to set email alerts
|

Recent malaria does not substantially impact COVID-19 antibody response or rates of symptomatic illness in communities with high malaria and COVID-19 transmission in Mali, West Africa

Abstract: Malaria has been hypothesized as a factor that may have reduced the severity of the COVID-19 pandemic in sub-Saharan Africa. To evaluate the effect of recent malaria on COVID-19 we assessed a subgroup of individuals participating in a longitudinal cohort COVID-19 serosurvey that were also undergoing intensive malaria monitoring as part of antimalarial vaccine trials during the 2020 transmission season in Mali. These communities experienced a high incidence of primarily asymptomatic or mild COVID-19 during 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Ecological research has demonstrated slightly earlier in the pandemic that COVID-19 infection rates and case fatality ratios tended to be lower in countries where malaria is endemic, and according to this research, COVID-19 treatment and prophylaxis may benefit from anti-malarial medications (such as hydroxychloroquine) ( Woodford et al, 2022 ). In March 2020, chloroqiune was added to the protocol of COVID-19 treatment by the National Health Committee (NHC) in China ( Woodford et al, 2022 ; Osei et al, 2022 ).…”
Section: Introductionmentioning
confidence: 77%
“…Ecological research has demonstrated slightly earlier in the pandemic that COVID-19 infection rates and case fatality ratios tended to be lower in countries where malaria is endemic, and according to this research, COVID-19 treatment and prophylaxis may benefit from anti-malarial medications (such as hydroxychloroquine) ( Woodford et al, 2022 ). In March 2020, chloroqiune was added to the protocol of COVID-19 treatment by the National Health Committee (NHC) in China ( Woodford et al, 2022 ; Osei et al, 2022 ).…”
Section: Introductionmentioning
confidence: 77%
“…There are several reports showing association between Neglected Infectious Diseases (NTDs) and SARS-CoV2, in terms of how they affect the severity of COVID-19 clinical outcomes, vice versa and the development of trained immunity as occurs for helminth infections and malaria (Ssebambulidde et al, 2020;Anyanwu, 2021;Gluchowska et al, 2021;Wilairatana et al, 2021;Achan et al, 2022;Hussein et al, 2022). Our review of literature indicate that the immunomodulatory effects of COVID-19 and parasitic co-infections brought insights not by direct investigations but based upon lessons learned from other co-infections systems (Fonte et al, 2020;Gluchowska et al, 2021;Akelew et al, 2022;Woodford et al, 2022). Briefly, helminth co-infection was suggested to cause immunomodulation in COVID-19 patients to result in reduction of disease severity (Bradbury et al, 2020).…”
Section: Co-infections With Sars-cov2mentioning
confidence: 87%
“…One possible explanation for this phenomenon is that malaria patients generate anti-GPI antibodies which eventually identify SARS-CoV-2 glycoproteins developing a protective response against COVID-19 improving the disease prognostic (Hussein et al, 2020). Conflicting results from a Malian longitudinal cohort study showed no association between malaria and COVID-19 seroconversion or effect on the symptoms reported for COVID-19 (Woodford et al, 2022). The identification of immunomodulatory effects provoked by malaria and helminth infections could lead us to better understanding of the factors involved in improvement of vaccine efficacy.…”
Section: Co-infections With Sars-cov2mentioning
confidence: 99%
“…This explanation suggests that by decreasing the body's inflammatory response to SARS-CoV2, exposure to malaria may reduce severe disease caused by COVID-19 (Guha et al 2021). Newer work in a longitudinal cohort finds no effect of malaria infection on COVID-19 incidence or symptom severity (Woodford et al 2022). Other mechanisms of protection have been proposed and are under examination (Orish et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Newer work in a longitudinal cohort finds no effect of malaria infection on COVID‐19 incidence or symptom severity (Woodford et al. 2022). Other mechanisms of protection have been proposed and are under examination (Orish et al.…”
Section: Discussionmentioning
confidence: 99%